Nowotwory złośliwe w Polsce jako problem zdrowia publicznego - Wojciechowska, Urszula; Didkowska, Joanna; Koćmiel, Agnieszka (Studia Demograficzne, 2012)
Malignant neoplasms are in Poland a major social problem not only in the older age groups, but they are the main cause of premature mortality (before age 65). This phenomenon is observed particularly in women – for several years cancer have been leading cause of death before age 65 (about 30% of deaths among young women and nearly 50% of deaths among middle-aged women). The projected increase in the number of cancer cases and deaths is attributable to demographic changes of the Polish population. Central Statistical Office in Poland estimates that the number of people over 65 years will increase by almost 75% by 2025. These changes translate into an increase in the number of new cases of the most common cancers in elderly (prostate, colon, lung among men and lung, breast, endometrial among women). The health phenomena taking place in the Polish population requires building a strong tool to monitor and analyze the processes involved. In case of cancer such tool is the cancer registry. In response to this need the National Cancer Registry launched a project aimed at creating a central database of cancers, establishing social baseline of conducting modern epidemiological research using information society technologies.